Use of an innovative electronic communications platform (912Rwanda) to improve prehospital transport of injured people in Rwanda: protocol for a type 2 hybrid effectiveness-implementation interrupted time series study - Antonio Belli; Karla Hemming; Justine Davies; Lucia D'Ambruoso; Laura Bojke; Sudha Jayaraman; Agnieszka Ignatowicz; Motunrayo Ajisola; Aurore Nishimwe; Jean Claude Byiringiro; Laura Quinn; Barnabas Tobi Alayande; et al. (BMJ Open)
Introduction Injury is a major cause of death in Rwanda, with many deaths occurring before hospital admission. Timely transport of injured patients to appropriate hospitals is crucial, ideally within an hour for severely injured patients. However, delays in reaching treatment facilities are common, with ambulance services using inefficient mobile phone communication. This project aims to evaluate the effectiveness and implementation of an innovative electronic communication platform (912Rwanda).Methods and analysis The study will be conducted through the public ambulance service, Service d’Aide Médicale d’Urgence (SAMU), and receiving health facilities in Kigali city and Musanze district in Rwanda. The 912Rwanda intervention will be rolled out in the two locations at different times. The primary effectiveness outcome is the time from ambulance deployment to patient arrival at the health facility. Secondary effectiveness outcomes include disaggregated times of the primary outcome and clinical outcomes, such as length of stay and requirement for intensive care. These outcomes will be evaluated using an interrupted time series analysis, accounting for non-homogeneous variances, auto-regressive errors and non-linear trends where appropriate. Implementation outcomes will be evaluated using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) Qualitative Evaluation for Systematic Translation (QuEST) framework. Cost-effectiveness will be evaluated using a cost-consequence analysis with consequences as determined by the interrupted time series analysis.Ethics and dissemination Ethical approval was obtained from the Rwanda National Research Ethics Committee (Ref No: 99/RNEC/2023). Dissemination will occur through open-access peer-reviewed publications, relevant national and international conferences.Trial registration number ISRCTN97674565.